ANALISIS KEGUNAAN LAPORAN KEUANGAN DALAM PENGAMBILAN KEPUTUSAN INVESTASI DI PASAR MODAL INDONESIA - TARMIZI ACHMAD (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2003)
One of the major objectives of financial statements is to supply financial information to user of financial information for decision making. This information should represent all of transactions and events that have happened in particular firms during one accounting period. Therefore, disclosure all of financial information relevant to a reporting company in financial statements is an important aspect of financial accounting.This research is undertaken to investigate whether accounting information presented by the Indonesian public companies still countains the qualities of relevance (Feedback, predicitive, and timeliness). This study also investigates how long should the financial statement can be accepted by users so that it did not lose its relevancy.Four group os users (investors, creditors, trustees, and stock and share brokers) are surveyed with a mailed questionnaires. The answered questionnaire, then, are analyzed by using statistical tests.The result of the data analysis show that the financial statements published by mostly by mostly Indonesian Public companies tends to produce irrelebant accounting information. This study also finds that the period between two and three months is mostly preferred by users of financial statements so that they did not lose their relevancy.